2016
DOI: 10.1113/ep085717
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II control of regional haemodynamics in rats with aortocaval fistula

Abstract: New Findings r What is the central question of this study?Hyperdynamic circulation because of arteriovenous fistula results in reduction of blood flow to organs but is a model of low circulatory resistance with activated renin-angiotensin system. The aim was to determine contributions of different subtypes of angiotensin II receptors to regional blood flow and vascular conductance in a hyperdynamic circulatory state. r What is the main finding and its importance?The renin-angiotensin system plays a pivotal rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…However, www.nature.com/scientificreports/ studies that utilized ACE inhibitors to reduce activated RAS failed to show an improvement in RBF 20,21 . Moreover, our results are in line with that of Duggan and Tabrizchi, who found that in acute settings, only losartan-infused ACF rats responded with an increase in RBF, dissimilar to rats infused with an ACE inhibitor captopril 22 . By contrast, a previous study that utilized the same ACEi treatment as in our study for five weeks in TGR rats with HF improved RBF 14 .…”
Section: Discussionsupporting
confidence: 93%
“…However, www.nature.com/scientificreports/ studies that utilized ACE inhibitors to reduce activated RAS failed to show an improvement in RBF 20,21 . Moreover, our results are in line with that of Duggan and Tabrizchi, who found that in acute settings, only losartan-infused ACF rats responded with an increase in RBF, dissimilar to rats infused with an ACE inhibitor captopril 22 . By contrast, a previous study that utilized the same ACEi treatment as in our study for five weeks in TGR rats with HF improved RBF 14 .…”
Section: Discussionsupporting
confidence: 93%
“…Large AVFs are used not only to study hemodynamics of hyperkinetic circulation, but also as an easily obtainable model of HF. They are usually created by a direct connection of aorta an inferior vena cava ( Modesti et al, 2000 ; Duggan and Tabrizchi 2016 ). However, all these techniques require participation of a skilled (vascular) surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, MAP changes after intravenous administration initiate some indirect effects, such as activation of SNS followed by its effects on peripheral and RVR [19]. It is noteworthy that initial studies in patients and animals with CHF evaluated renal vascular responses to systemic administration of vasoactive agents, which could result in misleading information regarding the role altered renal vascular responsiveness in the development of renal dysfunction in CHF [12,[54][55][56].…”
Section: Discussionmentioning
confidence: 99%